Method for manufacturing fine linear bodies
Patent Information
- Application Number
- JP2021032336
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-03
- Filing Date
- 2021-03-02
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2041-03-02
AI Technical Summary
【0007】 本発明の方法によれば、生産性よく金属の微細線状体を製造することが可能である。
Smart Images

Figure 0007645094000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing fine linear bodies having a metal base material. [Background technology]
[0002] Nanowires are expected to exhibit physical and chemical properties (e.g., electrical conductivity, thermal conductivity, luminescence properties, catalytic activity, etc.) not found in conventional materials due to their minute size, high aspect ratio, etc. The applicant previously proposed ultrafine metal filaments described in Patent Document 1 as a conventional technique related to such nanowires.
[0003] In Patent Document 1, ultrafine metal filaments are produced by electrolytically reducing metal ions in a nonaqueous electrolyte containing the metal ions. The metal ions are present in the nonaqueous electrolyte in the form of a stable complex. Specifically, a charge-neutralized body formed by electrically neutralizing the complex in an aqueous phase with a counter ion having an opposite charge to the complex is continuously extracted from the aqueous phase into the nonaqueous electrolyte, and the metal ions in the charge-neutralized body extracted into the nonaqueous electrolyte are electrolytically reduced. In the electrolytic reduction, a wire is used as a cathode, and the tip of the wire is opposed to the anode. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-299103 A Summary of the Invention [Problem to be solved by the invention]
[0005] According to the method described in Patent Document 1, it is possible to manufacture very thin and long ultrafine metal filaments. However, this method uses two phases, an aqueous phase and a non-aqueous electrolyte phase, which makes the manufacturing process complicated, and there is room for improvement in terms of industrial productivity. SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a method for producing fine metal filaments with good productivity. [Means for solving the problem]
[0006] The present invention provides a method for producing a fine linear body having a metal base material, the method comprising the steps of depositing a metal on a cathode by electrolytic reduction using an electrolyte solution containing a metal element source, the method comprising the steps of: The present invention provides a method for producing fine linear bodies, in which electrolytic reduction is carried out in a state in which an oily substance is present on the surface of the cathode. Effect of the Invention
[0007] According to the method of the present invention, fine metal filaments can be produced with good productivity. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a scanning electron microscope image of the fine linear bodies obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described below based on its preferred embodiments. The present invention relates to a method for producing fine linear bodies. In the following description, the term "fine linear body" may refer to an individual linear body or a collection of multiple linear bodies depending on the context. The fine linear body produced according to the production method of the present invention (hereinafter also referred to as "the present production method") is typically a linear body extending in one direction. The state in which the linear body extends in one direction varies depending on the state of the linear body when observed. For example, the linear body extends in a straight line or extends in one direction while meandering in a curved manner. This linear body is characterized by its long length despite being very thin.
[0010] In the present invention, an electrolytic method is preferably used for producing the fine linear bodies. The reason for this is that the electrolytic method allows repeated use of the electrolyte, and therefore less liquid is required for producing the fine linear bodies, and at the same time, the amount of waste liquid to be treated can be reduced. Another method for producing metal powder is the atomization method, but it is not possible to produce anisotropic shapes such as fine linear bodies. Another method is the wet reduction method, but this method does not allow repeated use of the solution and is also not possible to increase the concentration of the target metal element above a certain level, making it difficult to produce fine linear bodies with good productivity.
[0011] When producing fine linear bodies by electrolysis, for example, an anode and a cathode are immersed in a sulfuric acid electrolyte containing a metal element source, a direct current is passed therethrough to perform electrolytic reduction, and fine linear bodies are precipitated on the surface of the cathode, the precipitated fine linear bodies are scraped off and recovered by a mechanical or electrical method, and the recovered fine linear bodies are washed with water, dried, and sieved if necessary.
[0012] There is no particular restriction on the type of metal element used in the present manufacturing method, so long as the fine linear bodies can be manufactured by the present manufacturing method. Considering the balance between high electrical conductivity and ease of industrial use, examples of the metal elements include copper, zinc, tin, iron, nickel, cobalt, lead, bismuth, silver, gold, and platinum. These metal elements have in common that they can be electrolytically deposited from an aqueous solution, so they can be manufactured in the same manner according to the present manufacturing method, regardless of which metal element is used. Among these, it is particularly preferable to use copper or zinc as the base material. Note that "using copper or zinc as the base material" means that the proportion of copper or zinc in the fine linear bodies is 70 mass% or more, preferably 90 mass% or more. The fine linear bodies obtained by the present manufacturing method may be composed of only the desired metal element, excluding inevitable impurities, or may be composed of an alloy of the desired metal element, excluding inevitable impurities, or may be composed of a combination of two or more of the above-mentioned metal elements, excluding inevitable impurities.
[0013] When manufacturing fine filaments by the above-mentioned procedure, the inventors have found that it is advantageous to carry out electrolytic reduction with an oily substance attached to the surface of the cathode. By reducing the ions of the metal elements under such conditions, it is possible to control the reduction reaction. The details are as follows. The amount of oily substance to be attached to the cathode surface is expressed in thickness, and is on average several hundred nm or more, preferably several μm to several hundred μm. However, the thickness varies locally due to the fluctuation of the electrolyte. Although almost no metal ions coexist in the oily substance, the electrolyte containing metal ions may float in the form of droplets in the oily substance, or a very small amount of the electrolyte may be intermittently attracted to the vicinity of the electrode by the force of the electric field formed by applying electricity. Under such circumstances, a reduction reaction of the metal occurs on the surface of the cathode, and a metal protrusion is formed locally. The thickness of the oily substance directly above this protrusion is thinner than other parts, so the electrical resistance in that part decreases, the current becomes concentrated there, and the protrusion becomes linear and grows. In this way, fine metal filaments are formed by electrolysis.
[0014] Examples of the method of attaching the oily substance to the surface of the cathode described above include a method of directly applying the oily substance to the surface of the cathode, a method of immersing the cathode in a container containing the oily substance and attaching it to the surface of the cathode by floating the oily substance on the electrolyte and immersing the cathode from above. In addition, a method of suspending the oily substance in the electrolyte and stirring the suspended electrolyte so that the suspended oily substance hits the surface of the cathode and attaches to the surface of the cathode as it is can also be mentioned. In addition, if the oily substance has the property of dissolving in a small amount in the electrolyte, even if the suspended oily substance does not directly touch the electrode, the oily substance once dissolved in the electrolyte will continuously adsorb to the electrode surface and eventually adhere to the surface.
[0015] Examples of the oily substance to be attached to the surface of the cathode include various organic compounds that are poorly soluble or insoluble in water and have a viscosity sufficient to be retained on the surface of the cathode after being attached thereto. Note that "poorly soluble or insoluble in water" means that the compound dissolves in an amount of 100 g or less in 1 L of water at the temperature at which the fine linear bodies are produced. The oily substance may be liquid or solid. The oily substance may be dissolved in a liquid solvent at room temperature (20 to 30° C.) before use. For the purpose of making it easier to control the physical properties of the precipitated fine linear bodies, additives such as benzoic acid, fumaric acid, citric acid, benzotriazoles, etc. may be further used in the oily substance.
[0016] The organic compounds include, provided that they are poorly soluble or insoluble in water, aliphatic hydrocarbons, aromatic hydrocarbons, aliphatic alcohols, aromatic alcohols, aliphatic aldehydes, aromatic aldehydes, aliphatic ethers, aromatic ethers, aliphatic ketones, aromatic ketones, aliphatic carboxylic acids and their salts, aromatic carboxylic acids and their salts, amides of aliphatic carboxylic acids, amides of aromatic carboxylic acids, esters of aliphatic carboxylic acids, silicones (e.g., dimethyl silicones), aliphatic amines, aromatic amines, nitrogen-containing heterocyclic compounds, tributyl phosphate, thiols, fluorine-based solvents, ionic liquids, etc. In this specification, the term "aliphatic alcohol" refers to an alcohol having 5 or more carbon atoms. As a result of the inventor's investigations, it was found that fine filaments can be produced more successfully by using, as the oily substance, particularly, a fatty acid or a salt thereof, an ester thereof, or an amide thereof, an aromatic carboxylic acid, an aliphatic hydrocarbon, an aliphatic alcohol, an aliphatic amine, a silicone (e.g., dimethyl silicone), or a mixture thereof.
[0017] The fatty acid may be a lower fatty acid or a higher fatty acid. The lower fatty acid may be a saturated or unsaturated aliphatic carboxylic acid having preferably 9 or less carbon atoms. The higher fatty acid may be a saturated or unsaturated aliphatic carboxylic acid having preferably 10 to 25 carbon atoms, more preferably 10 to 22 carbon atoms, and even more preferably 11 to 20 carbon atoms. Examples of saturated aliphatic carboxylic acids include caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, margaric acid, stearic acid, nonadecylic acid, arachidic acid, henicosylic acid, behenic acid, tricosylic acid, and lignoceric acid.
[0018] The unsaturated aliphatic carboxylic acid includes those having one or more unsaturated carbon bonds in the molecule. Examples of unsaturated aliphatic carboxylic acids having one unsaturated carbon bond in the molecule include crotonic acid, myristoleic acid, palmitoleic acid, sapienic acid, oleic acid, elaidic acid, vaccenic acid, gadoleic acid, eicosenoic acid, erucic acid, and nervonic acid. Examples of unsaturated aliphatic carboxylic acids having two or more unsaturated carbon bonds in the molecule include linoleic acid, eicosadienoic acid, docosadienoic acid, and linolenic acid.
[0019] Examples of aromatic carboxylic acids include benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, hemimellitic acid, trimellitic acid, trimesic acid, mellophanic acid, prenitic acid, pyromellitic acid, mellitic acid, diphenic acid, toluic acid, xylyl acid, hemellitic acid, mesitylene acid, prenityl acid, and γ-isoduryl acid. duric acid, β-isodurric acid, mesic acid, α-isodurric acid, cumic acid, ubitolic acid, α-toluic acid, hydratropic acid, atropic acid, hydrocinnamic acid, cinnamic acid, salicylic acid, anisic acid, cresotinic acid, o-homosalicylic acid, o-cresotinic acid, m-homosalicylic acid, m-cresotinic acid, p-homosalicylic acid, p-cresotinic acid, o-pyrocatechuic acid, β-resorcylic acid, gentisic acid, γ-resorcylic acid, protocatechuic acid, α-resorcylic acid, vanillic acid, isovanillic acid, veratrum, o-veratric acid, orsellinic acid , m-hemipinic acid, gallic acid, syringic acid, asaronic acid, mandelic acid, vanillic acid, mandelic acid, homoanisic acid, homogentisic acid, homoprotocatechuic acid, homovanillic acid, homoisovanillic acid, homoveratric acid, o-homoveratric acid, homophthalic acid, homoisophthalic acid, homoterephthalic acid, phthalonic acid, isophthalonic acid, terephthalonic acid, benzilic acid, atrolactic acid, tropic acid, mellitic acid, phloretic acid, hydrocaffeic acid, hydroferulic acid, hydroisoferulic acid, p-coumaric acid, umbellic acid, caffeic acid, ferulic acid, isoferulic acid, sinapic acid, benzoyl, phthaloyl, isophthaloyl, terephthaloyl, toluic acid oil, xyloyl, cumoyl, α-toluoyl, hydroatropoyl, atropoyl, hydrocinnamoyl, cinnamoyl, salicyloyl, anisoyl, cresotoyl, o-pyrocatechuyl, β-resorcyloyl, gentisoyl, γ-resorcyloyl, protocatechuyl, α-resorcyloyl, vanilloyl, isovanilloyl, o-veratroyl, veratroyl, galloyl, syringoyl, mandeloyl, vanilmandeloyl, homogentisoyl, homovanilloyl, homoveratroyl, benzylloyl, tropoyl, caffeoyl, feruloyl, perbenzoic acid, ibuprofen, ketoprofen, and felbinac.
[0020] Among the above fatty acids, it is preferable to use a saturated aliphatic carboxylic acid or an unsaturated aliphatic carboxylic acid, since this makes it possible to more successfully produce the fine linear bodies.
[0021] The ester of the fatty acid is preferably an ester with a saturated aliphatic alcohol or an unsaturated aliphatic alcohol. The carbon number of the alcohol is preferably from 1 to 18. The ester of the fatty acid is more preferably an ester with a saturated aliphatic alcohol having from 1 to 18 carbon atoms. For example, ethyl acetate can be mentioned.
[0022] The amount of oily substance to be attached to the surface of the cathode is 0.1 g / m per unit surface area of the cathode. 2 More than 500g / m 2 It is preferable that the density is less than 1 g / m 2 More than 500g / m 2 More preferably, it is 3 g / m or less. 2 More than 200g / m 2 More preferably, it is 5 g / m or less. 2 More than 100g / m 2 It is even more preferable that:
[0023] The anode and cathode may be made of any known material without any particular limitations. For example, anodes and cathodes made of titanium or copper may be used. An insoluble metal electrode (DSE) may also be used for the anode. In this regard, the current density during reduction is 5A / m 2 More than 3000A / m 2 It is preferable that the resistance is less than 10 A / m 2 More than 1000A / m 2 More preferably, it is 50 A / m or less. 2 More than 500A / m 2 It is even more preferable that:
[0024] Usually, in the deposition of metals by electrolysis, a good surface shape can be obtained by passing an amount of electricity corresponding to a reduction rate slower than the supply rate of metal ions from the electrolytic solution (for example, in the case of plating, a state in which a metallic luster is obtained on the surface). Similarly, in the electrolysis of the present invention, it is preferable that the concentration of ions of metal elements in the electrolytic solution is a concentration that can supply metal ions without excess or deficiency to the reaction rate of reduction of the metal ions, and from this viewpoint, the concentration of metal ions is preferably 1 g / L or more and 80 g / L or less, and more preferably 3 g / L or more and 60 g / L or less. From the same viewpoint, it is preferable to stir or circulate the electrolytic solution in the electrolytic cell during electrolysis. The electrolyte may be used in an unheated state, such as at room temperature (25° C.), or in a heated state. From the same viewpoint, it is preferable to adjust the size of the electrolytic cell, the number of electrodes, the shape of the electrodes (plate-like, drum-like), the distance between the electrodes, and the amount of electrolyte circulation so as to constantly maintain a high metal ion concentration in the electrolyte near the electrodes.
[0025] The fine linear bodies thus produced are very thin, preferably having a thickness of 30 nm to 10 μm, more preferably 30 nm to 1000 nm, even more preferably 40 nm to 500 nm, and even more preferably 45 nm to 300 nm. Despite being very thin, the fine linear bodies are long, preferably having a length of 0.3 μm to 300 μm, more preferably 0.5 μm to 100 μm, even more preferably 2 μm to 70 μm, and even more preferably 2 μm to 50 μm. By combining such thickness and length, the fine linear bodies are easy to handle and can have excellent filling properties when used, for example, as a bonding material. In addition, the aspect ratio (length of fine linear bodies [m] / thickness of fine linear bodies [m]) is preferably 5 or more and 2500 or less, more preferably 10 or more and 2500 or less, even more preferably 40 or more and 2500 or less, and even more preferably 40 or more and 1500 or less. The thickness of the fine filaments is measured by observation under an electron microscope, and their length is measured by panoramic stitching of electron microscope photographs.
[0026] The fine linear bodies obtained by this manufacturing method may have a shape in which the thickness is almost uniform over their entire length, or a shape in which the thickness is not uniform but is beaded. The fine linear bodies obtained by this manufacturing method have at least one end tapered. The "tapered shape" refers to a shape in which, when observing the end region of the fine linear bodies, the thickness gradually decreases toward the tip.
[0027] The shape of the fine linear bodies obtained by this manufacturing method is typically linear bodies extending in one direction, and the fine linear bodies may or may not have a main chain portion extending in one direction and a branched structure branched from the middle of the main chain portion. From the viewpoint of imparting sufficient conductivity to the object with a small amount and from the viewpoint of making it difficult for the conductivity of the object to decrease when the conductive object is stretched or bent, it is preferable that the fine linear bodies have a non-branched structure having only the main chain portion. On the other hand, from the viewpoint of the aggregate of the fine linear bodies exhibiting a bulky structure, it is preferable that the fine linear bodies have one or more branched parts. When the fine linear bodies have a branched part, it is preferable that the thickness at the parts before and after the branching is substantially the same from the viewpoint of making it easier for the aggregate of the linear bodies to exhibit a cotton-like bulky structure.
[0028] When the fine linear bodies obtained by the present production method are an aggregate containing a plurality of fine linear bodies, the aggregate may contain particles having a shape other than that of linear bodies, although it is preferable that particles having a shape other than that of linear bodies are not present in the aggregate as much as possible from the viewpoint of preventing a decrease in electrical conductivity even when the aggregate is subjected to deformation such as bending or stretching. When the ratio of particles having a shape other than linear bodies in the aggregate is defined as the "irregularity ratio," the irregularity ratio is preferably 50% or less, more preferably 30% or less, and even more preferably 20% or less. By producing fine linear bodies by this production method, it is possible to easily achieve an irregularity ratio of 50% or less. The irregularity rate is determined by observing the sample under a scanning electron microscope (hereinafter referred to as "SEM") and calculating the percentage of [area of irregular shapes / area of fine linear bodies] in a 5000x field of view. "Irregular shapes" refers to shapes other than linear bodies (e.g., spheres, lumps, fern-like leaves, etc.).
[0029] The fine linear bodies obtained by this manufacturing method may have a structure having a main body made of a first metal element or an alloy of the first metal element, and a coating layer of a second metal element other than the first metal element arranged on the surface of the main body. Examples of the first metal element include copper, zinc, tin, iron, nickel, cobalt, lead, bismuth, silver, gold, and platinum, as described above. Examples of the second metal element include silver, cobalt, iron, nickel, zinc, lead, tin, platinum, gold, palladium, etc., and alloys containing one or more of these metals (e.g., nickel alloys, iron alloys, etc.), provided that the second metal element is different from the first metal element. In particular, it is preferable that the second metal element has a higher conductivity than the first metal element constituting the main body or an alloy of the metal element, from the viewpoint of further increasing the conductivity imparted to the target object. From this viewpoint, when the first metal element is copper or zinc, it is preferable that the second metal element is silver.
[0030] As a method for forming a coating layer on the surface of the main body, for example, the main body can be formed by the above-mentioned method, followed by applying a catalyst that enables displacement plating or electroless plating to the fine linear body, and then plating the desired metal, or formation by a dry method is also possible.
[0031] The fine linear bodies obtained by this manufacturing method can be combined with other substances to impart electrical conductivity to the substances. For example, the fine linear bodies obtained by this manufacturing method can be combined with other metal elements to form a bonding material, and the bonding material can be sintered to form a sintered body. These bonding materials and sintered bodies are used, for example, as materials for bonding semiconductor chips and substrates. Moreover, the fine linear bodies obtained by the present production method can be incorporated into a resin to obtain a resin composition containing the fine linear bodies and the resin. The resin composition exhibits electrical conductivity by containing the fine linear bodies. To impart electrical conductivity to a resin, for example, fine linear bodies may be dispersed in the resin. Alternatively, a layer containing fine linear bodies may be formed on the surface of a substrate containing a resin. In either embodiment, the resin composition can be molded into various shapes. For example, it can be molded into one-dimensional shapes such as fibers, two-dimensional shapes such as films, plates, and strips, and various three-dimensional shapes. In either shape, the resin composition exhibits sufficient electrical conductivity with the addition of a relatively small amount of fine linear bodies. The resin composition differs from conventional conductive resin compositions containing copper powder as a filler in that the electrical conductivity of the resin composition is low before and after stretching or bending the resin composition. From this perspective, when the resin composition is stretchable or bendable, the characteristics of the fine linear bodies of the present invention are effectively exhibited. Conventional conductive resin compositions tend to be easily reduced in electrical conductivity when stretched or bent.
[0032] The resin composition containing the fine filaments obtained by this production method and a resin is suitable for use in applications requiring electrical conductivity and in which deformation occurs due to an external force, such as wearable devices such as bioelectrodes and flexible displays. EXAMPLES
[0033] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".
[0034] Example 1 In this example, a fine linear body made of copper was produced. An electrolyte solution was prepared from copper sulfate and sulfuric acid so that the copper ion concentration was 4g / L and the free sulfuric acid concentration was 5g / L, and 800mL of the solution was placed in an electrolytic cell measuring 10cm x 8cm x 12cm (capacity approximately 1000mL) and stirred. The temperature of the electrolyte solution was 40℃. A copper plate measuring 8 cm × 8 cm was used as the cathode. Oleic acid was evenly applied to the surface of the cathode. The amount of application was 7 g / m. 2 A copper plate measuring 8 cm x 8 cm was used as the anode. The cathode and anode were suspended in the electrolytic cell so that the distance between them was 8 cm. Current density is 160A / m 2 The electrolysis was carried out for 30 minutes at a temperature of 100° C. In this manner, copper was electrodeposited on the surface of the cathode. The copper electrodeposited on the surface of the cathode was collected and washed with ethanol. When the obtained deposit was observed using an SEM, fine filaments were confirmed. The irregularity rate was 1%. The filaments were 50 nm in diameter and 2.6 μm in length, with each end tapering. The diameter of the fine filaments was obtained by arithmetically averaging the diameters of 10 filaments from a 20,000x SEM image. The length was obtained by arithmetically averaging the lengths of 20 filaments from a 10,000x SEM image. The productivity of the fine linear bodies was about 1.5 g per hour for an electrolyte amount of 1 L. Moreover, an SEM image of the fine linear bodies obtained in Example 1 is shown in FIG.
[0035] Example 2 In this example, fine filaments made of zinc were produced. An electrolyte solution was prepared from zinc sulfate and sulfuric acid so that the zinc ion concentration was 50g / L and the free sulfuric acid concentration was 25g / L, and 800mL of the solution was placed in an electrolytic cell measuring 10cm x 8cm x 12cm (capacity approximately 1000mL) and stirred. The electrolyte temperature was set to 40℃. The same 8 cm x 8 cm copper plate as in Example 1 was used as the cathode. Oleic acid was uniformly applied to the surface of the cathode. The amount of application was 20 g / m. 2An 8 cm x 8 cm insoluble metal electrode (DSE De Nora Permelec) was used as the anode. Both electrodes were suspended in the electrolytic cell so that the distance between the cathode and anode was 8 cm. Current density is 160A / m 2 The electrolysis was carried out for 30 minutes at a temperature adjusted to 0.5° C. In this manner, zinc was electrodeposited on the surface of the cathode. The zinc electrodeposited on the surface of the cathode was collected and washed with acetone. The resulting electrodeposit was observed using a SEM, and fine linear bodies were confirmed. The irregularity rate was 20%. The linear bodies were 5 μm in diameter and 50 μm in length, with each end tapered. The productivity of the fine filaments was about 1.5 g per hour for 1 L of electrolyte.
[0036] Comparative Example 1 This comparative example corresponds to Example 1 of Patent Document 1. Put 0.72 g of copper oxide (I), 7.5 ml of 64% sulfuric acid, 8.6 ml of acetonitrile, 1 g of sodium chloride, and pure water into a beaker and stir thoroughly to obtain copper (I) acetonitrile complex [M m L x ] and chloride ions〔Y n ] and a charge-neutralized complex [M m L x 〕 s [Y n 〕 t The temperature of the aqueous phase was 25° C. Separately from the aqueous phase, 90 ml of MIBK as a non-aqueous electrolyte and 0.05 g of TBAP as a supporting salt were placed in a beaker and thoroughly stirred to obtain an organic phase consisting of a low-conductivity non-aqueous electrolyte. A platinum electrode as a cathode, a copper electrode as an anode, and a stirrer were set in a beaker. The anode was set through an insulating sleeve. The aqueous phase and the organic phase were put into the beaker in equal volumes, and electrolytic reduction was carried out by constant potential electrolysis while gently stirring with a stirrer. The electrolytic reduction was carried out using a non-aqueous solvent reference electrode (Ag / Ag +) at a potential of -1.5 V. The multiple linear bodies produced by electrolytic reduction were slowly pulled out of the organic phase and dried to obtain an assembly in which the bodies were aligned in one direction. A portion of the linear bodies was taken from the resulting assembly and observed by SEM, confirming that they were fine linear bodies. The linear bodies were 50 nm in diameter and 5 cm in length. The productivity of the fine filaments was about 0.02 g per hour for 1 L of electrolyte.
Claims
1. A method for producing a fine linear body having a thickness of 30 nm to 10 μm, a length of 0.3 μm to 300 μm, an aspect ratio defined as length / thickness of 5 to 2500, and having a non-branched structure or one branched portion, the method comprising the steps of: The method includes a step of depositing a metal on a cathode by electrolytic reduction using an electrolyte solution containing a metal element source, carrying out electrolytic reduction in the presence of an oily substance on the surface of the cathode; The method for producing fine filaments, wherein the oily substance contains a higher fatty acid having 10 to 25 carbon atoms or a salt thereof.
2. The manufacturing method described in claim 1, wherein the oily substance has a solubility of 100 g or less per 1 L of water.
3. The method of claim 1, wherein the amount of the oily substance present on the surface of the cathode is 5 g / m 2 or more and 100 g / m 2 or less per unit surface area of the cathode.
4. The method according to any one of claims 1 to 3, wherein the metal element is copper, zinc, tin, iron, nickel, cobalt, lead, bismuth, silver, gold or platinum.
5. A method for causing the oily substance to be present on the surface of the cathode, comprising: A method of directly applying the oily substance to the surface of the cathode; A method of immersing the cathode in a container containing the oily substance and attaching it to the cathode; A method in which the oily substance is floated on the electrolyte and the cathode is immersed in the electrolyte from above to cause the oily substance to adhere to the surface of the cathode; or The method according to any one of claims 1 to 4, comprising suspending the oily substance in the electrolyte and stirring the suspended electrolyte to cause the suspended oily substance to adhere to the surface of the cathode.
Citation Information
Patent Citations
Method for preparation of fine lead powder by electrodeposition
CN104131317A
Method for preparing micron-sized monodisperse silver powder based on electrochemical deposition method
CN114540881A
Ultrafine metal wire body and manufacturing method thereof
JP2009299103A
Sulfuric acid-based copper electrolyte, and production method of dendrite-like copper powder using the same
JP2015168867A
Commutator
JP2019216524A